Fronthaul m??vel com amplifica????o de RF no dom??nio ??ptico para redes 5G - Lima, Eduardo Saia (2019)
This work reports the concept and implementation of a mobile fronthaul with photonics-assisted RF amplification, aiming the fifth generation of mobile networks (5G). The fronthaul takes advantage of using a photonics-based RF amplifier (PBRA), which provides RF gain using four-wave mixing optical nonlinear effect. New amplification architectures are proposed for minimizing the Brillouin optical nonlinear effect, enabling to enhance the PBRA energetic efficiency, maximize its performance and minimize its cost. It points out the optical amplifier elimination from the PBRA setup, baseband signal amplification and RF gain up to 26 dB from 300 kHz to 50 GHz, with the purpose of illustrating the applicability for all mobile network generations. Experimental results demonstrate a 27 Gbit/s mobile fronthaul, operating simultaneously in the 7.5 and 28 GHz bands, and fiber-wireless system with 10 Gbits/s throughput.